A Case Series of Recreational Ketamine-Induced Cholangiopathy - Larisa K. Garkusha; Zhongqian Lin; Linda A. Lee (Annals of Internal Medicine: Clinical Cases)
Ketamine, a dissociative anesthetic, is growing in popularity among young adults as a “club drug” in the U.S. Chronic use may lead to dependence and withdrawal symptoms, but ketamine also has been associated with ulcerative cystitis. We describe severe cholestasis and cholangiopathy in 6 young adults with chronic recreational ketamine use. All presented with progressive abdominal pain and cholestasis, sometimes with concomitant urinary symptoms and weight loss. In each case, there was marked biliary duct dilatation without evidence of obstruction, suggestive of sclerosing cholangitis. In some cases, the biliary duct dilatation was reversible with cessation of ketamine use.